Safety assessment of moso bamboo column under fire by using bamboo as protection layer - Fitriana, Laila; Tsai, Mengting (Institut Teknologi Sepuluh Nopember, 2017)
Global warming issue has forced the construction world including architecture to find the green material in order to minimize CO2 which damages to the nature. In the beginning, wood was one of the green material but it has long growth cycle. Lately, bamboo has been chosen for its fast growing cycle and resuming some wood properties, also known as local material and eco-friendly –benign to the nature. Generally, wood and bamboo are composed by carbon-based compound. So, they are combustible and flammable when they are exposed to the fire. Up to now, there are not so many studies regarding the fire behavior of raw round bamboo which is used as the structure. To investigate the effectiveness of bamboo protection layer, the nine-trunk bamboos will be tied up to construct the column. A one bamboo will be placed in the middle and surrounded by the other eight-bamboos –as the protection layer of the center. All of them are with no-fire retardant. By doing this, it is possible to obtain knowledge upon bamboo on its natural properties. Specimen will be exposed to the fire inside the furnace up to 700° C. The temperature changing on the specimen will be measured by thermocouples which are installed inside and outside the wall of main bamboo in the center part. The main bamboo is expected to have lower temperature than its auto-ignition temperature, so that the structure will be able stand out during the fire until the occupants able to be evacuated safely.